Evaluation of temporal and spatial changes of global ecosystem health. (20th November 2020) - Ran, Chen; Wang, Shijie; Bai, Xiaoyong; Tan, Qiu; Wu, Luhua; Luo, Xuling; Chen, Huan; Xi, Huipeng; Lu, Qian
Abstract: Understanding the spatial distribution pattern and driving factors behind ecosystem health is beneficial to ecosystem management and restoration. However, the literature shows little in‐depth exploration of regional heterogeneity and the factors that influence ecosystem health on a global scale. This study assesses global ecosystem health for the period 2000–2015 based on the vigor, organization, resilience, and service (VORS) model, and it explores the factors that influence regional differences in ecosystem health. Our results show that: (a) regions with high levels of ecosystem health are distributed mainly near the Equator and within the north–south regression line (0°N–13°N, 0°S–18°S); (b) seven critical zones with high levels of ecosystem health are identified (13°N–18°S, 45°N–65°N, 35°S–56°S, 47°W–80°W, 120°W–130°W, 8°E–37°E, 92°E–157°E); and (c) average annual precipitation and soil moisture play a key role in ecosystem health globally, with correlations of 0.574 and 0.399, respectively. Socioeconomic factors act as bridges, linking and reinforcing the influence of other factors in areas with medium to low levels of ecosystem health. Our study contributes to better understanding of ecosystem health, fills gaps in global ecosystem health diagnosis, and provides reference points for management and recovery of ecosystems.